A Study on Surface Roughness and Cutting Width for Circular Contour Machining of Stir Cast AA6063/SiC Composites in WEDM (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Wire electrical discharge machining is used in machining electric conductive materials with intricate shapes and profiles. This paper presents an experimental investigation on the influence of cutting conditions of WEDM on surface roughness and cutting width of machining of AA6063/SiC composites. Here a semi cylindrical piece is removed from a rectangular plate of AA6063/SiC composites plate fabricated with reinforcing SiC in 0%, 5%, 10% and 15% weight fractions through stir casting. The effect of WEDM parameters such as pulse on time, pulse off time and peak current on surface roughness and cutting width on different composition of AA6063/SiC were analyzed for circular contour machining. The experimental results show that increase in percentage of SiC has high influence in mechanical behavior of AA6063/SiC composites and the effect of pulse on time is very significant in reducing the surface roughness and pulse off time plays an important role in producing minimum cutting width.